The Effect of Commercial Cow's Milk on the Quality of Kefir Fermentation - Kurnia, Nani; Mu'nisa, Andi; Amboupe, Dewi Sartika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Kefir is a dairy product derived from the fermentation of milk by kefir grains. Kefir grains are natural starter cultures in the form of small spheres containing various microorganisms, including bacteria and fungi. This study aims to evaluate the effect of milk medium type and initial weight of kefir grains on four fermentation parameters: curd, whey, pH, and kefir grain weight gain. The materials used in this study were natural starter cultures in the form of kefir grains and packaged cow's milk from various brands (A, B, D, F, and G) with differing nutritional compositions, as well as bulk cow's milk (C and E). The kefir production process began by mixing 250 ml of commercial cow's milk from various brands with kefir grains. The mass of kefir grains used was varied at 10 grams and 12 grams. Data analysis was performed using the Two-Way ANOVA method and Duncan's Multiple Range Test (DMRT). Based on the results of the Two-Way ANOVA test, it was found that the type of milk medium had a significant effect on three main parameters, namely curd (p-value = 0.000), whey (p-value = 0.000), and pH (p-value = 0.021), but did not have a significant effect on the increase in kefir grains (p-value = 0.676). Conversely, the initial weight of kefir grains only significantly affected kefir seed growth (p = 0.003) but not the other parameters. Packaged milk with higher nutritional content produces higher curds and lower whey, thereby potentially producing higher quality kefir. These results indicate that the type and nutritional content of milk affect the quality of kefir fermentation.